A coesão referencial em textos do gênero conto de terror: um trabalho com alunos dos anos finais do ensino fundamental a partir das sequências didáticas - Tortelli, Denise Menin (2017)
This master's research arises from a concern frequently discussed by professors in the Portuguese Language area - in which I include myself as a teacher and researcher: how to work textual production in the classroom in a meaningful way for the student, making him realize in what points presents difficulties in the language, looking for alternatives to solve them within the totality of the text. Therefore, starting from an interactionist proposal of language, we have as general objective to investigate the referential - and lexical - cohesion in texts of the horror short stories genre written by students of the 8th and 9th years of a public elementary school located in the city of Santa Maria, RS, during twelve workshops of textual production. In addition to working on referential cohesion, we also detected, in the course of the work, other aspects that were prejudicing textuality in texts and needed intervention, such as the construction of paragraphs and periods and the inappropriate use of punctuation marks. As a specific objective, we seek to ascertain if (and in what way) the Didactic Sequences (SD) methodological tool, associated with a textual genre as a mediating instrument, can help teachers in the task of qualifying students' written productions, linguistic weaknesses. To achieve our objectives, we developed textual production workshops to deal with the problems of referential (or remissive) and lexical cohesion found in texts, as well as the inappropriate use of punctuation marks and the construction of paragraphs and periods. For this, based on the studies of Vygotsky regarding the processes of internalization, we started with the methodology Didactic Sequences, developed by Dolz, Noverraz and Schneuwly (2004) and made an adaptation of the method to our reality, articulating it to Action Research PA), Thiollent (2011), in the construction of textual production workshops and support activities. In order to work on issues related to textual cohesion, we focus on the Linguistics of the Text and the works of Fávero (2009) and Koch (2014). For the purpose of the research, we analyzed four texts written by our subject, as well as some support activities, with the purpose of verifying the movements that made in the qualification of its text on the referential and lexical cohesion and other verified aspects. After the development of the research, we can observe a comparison between the diagnostic text, written by S.12 in the first workshop, and the last version of the "text of the mirror", a great evolution in some factors, both referring to gender and linguistic issues.